Identifying the Risk Factors Associated With Microalbuminuria in Patients with Type 2 Diabetes Mellitus - Mohamed Salahuddin; Mohammed Shaji P P (Asian Journal of Medical Research, 2020)
Background: To identify the risk factors associated with microalbuminuria in patients with type 2 diabetes mellitus. Subjects and Methods: The present study was conducted at diabetic clinic of NIMS hospital, a secondary care hospital in Wandoor, Malappuram district, Kerala. From all patients, urine sample was obtained. Ratio of albumin to creatinine of less than 30 mg/g is considered normal. The ratio between 30-300 mg/g signifies microalbuminuria and values above 300 mg/g is considered macroalbuminuria. Risk factors for microalbuminuria was recorded. Results: Out of 300 patients, 82 82 (27.33 %) had microalbuminuria. 63% of the study population had a total cholesterol more than 200 mg/dl. 65% of them had a serum triglycerides more than 200 mg/dl and 42% had serum HDL less than 40 mg/dl. Age more than 60 years and duration of diabetes more than 10 years had a significant relationship with microalbuminuria with p value less than 0.001. FBS more than 126 mg/dl, HBA1c more than 6.5 and serum creatinine more than 1.2 mg/dl had a significant relationship with presence of microalbuminuria. Lipid parameters did not have a statistically significant relationship with microalbuminuria. Age, duration of diabetes, fasting blood sugar, glycosylated haemoglobin and serum creatinine have p values less than 0.05. But duration of diabetes does not have odds ratio more than 1. Conclusion: The prevalence of microalbuminuria was 27.33%. Age more than 60 years and duration of diabetes more than 10 years had a significant relationship with microalbuminuria with p value less than 0.001. Variables like smoking, alcohol, blood pressure and BMI did not have any statistically significant relationship with microalbuminuria. FBS more than 126 mg/dl, HBA1c more than 6.5 and serum creatinine more than 1.2 mg/dl had a significant relationship with presence of microalbuminuria. Lipid parameters did not have a statistically significant relationship with microalbuminuria.